Recombinant leptospiral immunoglobulin like B protein based latex agglutination test for serodiagnosis of human leptospirosis (Asian Journal of Medical and Biological Research, 2020)
Humans get leptospirosis by contact with fresh water, damp soil, or vegetation contaminated by the urine of infected animals, swallowing contaminated food or water or while working in contaminated flood plains or at wet agricultural settings. The bacteria enter the body through abrasions in the skin and mucous membranes. In the present study recombinant LigB protein is employed in latex agglutination test, which is a cross reacting lipoprotein able to detect acute infection caused by any pathogenic leptospiral serovars. It was employed for serodiagnosis of leptospirosis. The 46 KDa 6X His tagged LigB protein, obtained by IPTG induction of recombinant E. coli M15 cells containing the N-terminal region of LigB gee in PQE30 expression vector, was purified by Ni-NTA affinity chromatography and adsorbed on latex bead surface for performing latex agglutination test against leptospirosis suspected human sera. A total of 28 human sera samples were received from Post Graduate Institute of Medical Education & Research (PGIMER), Chandigarh India, which tested positive by IgM ELISA test kit were subjected to both rLigB based LAT and MAT. All the 28 sera showed seropositivity by both the tests. Icterohaemorrahigae was the predominant serovar followed by Javanica and Grippotyphosa. Six out seven sera samples received from Indian Veterinary research Institute, Human Hospital and City Hospital, Bareilly were tested positive both by rLAT and MAT. The result showed that sera were tested positive by rLigB based LAT, which were reconfirmed using microscopic agglutination test (MAT). The results from LAT were in concordance with MAT. In conclusion, rLigB based LAT is a rapid, reliable diagnostic tool at resource poor and remote diagnostic centers with high sensitivity and specificity, under laboratory and field conditions, for the detection of leptospirosis.Asian J. Med. Biol. Res. June 2020, 6(2): 229-236